2013
DOI: 10.1073/pnas.1222154110
|View full text |Cite
|
Sign up to set email alerts
|

Neural predictors of individual differences in response to math tutoring in primary-grade school children

Abstract: Now, more than ever, the ability to acquire mathematical skills efficiently is critical for academic and professional success, yet little is known about the behavioral and neural mechanisms that drive some children to acquire these skills faster than others. Here we investigate the behavioral and neural predictors of individual differences in arithmetic skill acquisition in response to 8-wk of one-to-one math tutoring. Twenty-four children in grade 3 (ages 8-9 y), a critical period for acquisition of basic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
258
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(275 citation statements)
references
References 54 publications
11
258
4
2
Order By: Relevance
“…37 A similar conclusion is drawn from a study examining mathematical achievement, which shows that individual responses to 8 weeks of training can be predicted by brain anatomy and functional connectivity measures recorded before training; this is the connectivity and cortical indices of hippocampus and basal ganglia, but not of parietal areas-sites of learning typically engaged during mathematical problem solving. 38 These cognitive neuroscience findings can inform, and be informed by, developmental theorising; they support theories that explain learning in terms of brain-operator processes that are not contentor material-specific (e.g., visual-spatial or verbal), because these brain regions (basal ganglia, thalamus and hippocampus) have complex coordinating functions that apply across content domains. Problem solving and complex learning processes are clearly mediated in the brain through prefrontal-basal-gangliathalamus pathways.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 75%
“…37 A similar conclusion is drawn from a study examining mathematical achievement, which shows that individual responses to 8 weeks of training can be predicted by brain anatomy and functional connectivity measures recorded before training; this is the connectivity and cortical indices of hippocampus and basal ganglia, but not of parietal areas-sites of learning typically engaged during mathematical problem solving. 38 These cognitive neuroscience findings can inform, and be informed by, developmental theorising; they support theories that explain learning in terms of brain-operator processes that are not contentor material-specific (e.g., visual-spatial or verbal), because these brain regions (basal ganglia, thalamus and hippocampus) have complex coordinating functions that apply across content domains. Problem solving and complex learning processes are clearly mediated in the brain through prefrontal-basal-gangliathalamus pathways.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 75%
“…A somewhat different result was reached by Supekar et al (2013) who carried out functional and structural MRI analyses on grade 3 children (aged 8-9) prior to an intensive eight-week one-on-one math tutoring programme that focused on conceptual aspects of number knowledge and speeded practice on counting strategies (conceptual and procedural skills, respectively). The critical finding was that hippocampal volume and intrinsic connectivity of the hippocampus with dorsolateral and ventrolateral prefrontal cortices and the basal ganglia predicted training gains, whereas various behavioral measures did not.…”
Section: )mentioning
confidence: 99%
“…To examine the robustness and reliability of these particular brain connections for predicting social communication scores, we performed a support vector regression (SVR) analysis (24)(25)(26). Results showed that the strength of each of these brain connections was a reliable predictor of social communication function (left aSTS gPPI seed to left NAc: r = 0.62, P < 0.001; to right amygdala: r = 0.49, P = 0.004; to right hippocampus: r = 0.59, P < 0.001; to right fusiform: r = 0.54, P = 0.002; right pSTS gPPI seed to right OFC: r = 0.58, P < 0.001; to right AI: r = 0.66, P < 0.001; to right dACC: r = 0.66, P < 0.001).…”
Section: Individual Differences In Functional Connectivity During Motmentioning
confidence: 99%